Investigating ethnic identity development through storytelling: The conceptual and methodological potential of narrative approach - Ignjatović Natalija; Radosavljević Jovan; Simić Nataša (Psihološka Istraživanja)
This review paper critically reassesses the traditional quantitative approach to ethnic identity research and advocates for an alternative narrative methodology. Using Phinney's status model as a starting point, we propose a shift towards a more comprehensive narrative perspective in investigating ethnic identity development. Despite their contribution, survey-based studies face limitations in explaining the nuanced developmental process and contextual influences on identity changes, particularly ethnic exploration. Embracing ethnic labels shapes adolescents' relations with others, their experiences, actions, and available resources, involving the construction of a narrative about the meaning of belonging to a specific group. The narrative approach explores subjective significance of ethnic experiences, portraying identities as dynamic. It challenges the concept of abrupt transitions, shedding light on the gradual nature and intricacies of ethnic identity changes. Narratives offer a unique lens to understand the content of ethnic identity, revealing attitudes, beliefs, and cultural behaviours which remain unattainable when assessed using the ratingscale instruments. We examine the studies which use narratives, describe the methodology applied to the field of ethnic identity development and critically evaluate its implementation. In addition to recognizing the transformative potential of the narrative practice, the paper also acknowledges its limitations, including time and resource demands, as well as training requirements and analytical complexity. In conclusion, we suggest the exploration of new directions in ethnic identity development research, highlighting the potential benefits of integrating the qualitative methods, particularly narratives. This alternative approach could play a significant role in fostering deeper understanding of ethnic identity in contemporary landscapes.